Sustainable Transmitters for High-Capacity Metro-Access Networks - Stefano Gaiani; Alberto Gatto; Paola Parolari; Pierpaolo Boffi (IEEE Access)
Single sideband (SSB) modulation enables high spectral efficiency, and ensures high throughput performance when combined with discrete multitone (DMT) modulation. The conventional approach for generating SSB signals involves an IQ modulator to combine a pair of signals related by the Hilbert transform. However, this method relies on a power-intensive device, less suitable for intensity-modulation direct-detection (IM-DD) systems in metropolitan-access networks. In this paper, we analyze and compare various architectures for achieving SSB modulation in a more sustainable way, either through optical filtering or by satisfying the Hilbert transform condition using less power-intensive devices. Specifically, we focus on a sustainable approach, addressed as the dual-modulator (DM) scheme, which is implemented by cascading a directly modulated VCSEL with a Mach-Zehnder modulator. At the receiver side, SSB modulation enables the use of a Kramers-Kronig (KK) receiver, providing an efficient compensation of chromatic dispersion. The comparison of the considered schemes is achieved by a suitable simulation tool that features the generation of a SSB-DMT signal, its propagation in an uncompensated single mode fiber, its detection with a KK receiver, and the subsequent signal processing and data decoding. The simulations evaluate the performance of the various architectures in terms of capacity as a function of the propagation distance (up to 50 km), comparing also the associated signal to noise ratio curves. The proposed VCSEL-based DM scheme appears to offer an excellent trade-off between performance and implementation complexity, supporting high throughput, high spectral efficiency, thanks to SSB-DMT modulation.